2018
DOI: 10.1080/19382014.2018.1502521
|View full text |Cite
|
Sign up to set email alerts
|

Neprilysin inhibition in mouse islets enhances insulin secretion in a GLP-1 receptor dependent manner

Abstract: Neprilysin, a widely expressed peptidase upregulated in type 2 diabetes, is capable of cleaving and inactivating the insulinotropic glucagon-like peptide-1 (GLP-1). Like dipeptidyl peptidase-4 (DPP-4), inhibition of neprilysin activity under diabetic conditions is associated with increased active GLP-1 levels and improved glycemic control. While neprilysin expression has been demonstrated in islets, its local contribution to GLP-1-mediated insulin secretion remains unknown. We investigated in vitro whether isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…This is supported by recent studies in humans treated with ARNi [17,22], and by observations in animals [12,23]. We have shown that inhibition of islet neprilysin in vitro enhances both glucose-and GLP-1-mediated insulin secretion in a GLP-1 receptor-dependent manner, raising the possibility that islet neprilysin inhibition improves beta cell function by preserving islet-and/or gut-derived active GLP-1 [23]. Moreover, we demonstrated in vivo in high-fat fed, neprilysin-deficient mice that elevated active GLP-1 levels in plasma were associated with improved glucose tolerance as a result of enhanced beta cell function and insulin sensitivity [12].…”
Section: Evidence For a Beneficial Effect Of Neprilysin Inhibition Onsupporting
confidence: 64%
See 2 more Smart Citations
“…This is supported by recent studies in humans treated with ARNi [17,22], and by observations in animals [12,23]. We have shown that inhibition of islet neprilysin in vitro enhances both glucose-and GLP-1-mediated insulin secretion in a GLP-1 receptor-dependent manner, raising the possibility that islet neprilysin inhibition improves beta cell function by preserving islet-and/or gut-derived active GLP-1 [23]. Moreover, we demonstrated in vivo in high-fat fed, neprilysin-deficient mice that elevated active GLP-1 levels in plasma were associated with improved glucose tolerance as a result of enhanced beta cell function and insulin sensitivity [12].…”
Section: Evidence For a Beneficial Effect Of Neprilysin Inhibition Onsupporting
confidence: 64%
“…One potential mechanism by which neprilysin inhibition improves glucose homeostasis may be by increasing levels, and thereby the insulinotropic effects, of GLP-1 [2,3]. This is supported by recent studies in humans treated with ARNi [17,22], and by observations in animals [12,23]. We have shown that inhibition of islet neprilysin in vitro enhances both glucose-and GLP-1-mediated insulin secretion in a GLP-1 receptor-dependent manner, raising the possibility that islet neprilysin inhibition improves beta cell function by preserving islet-and/or gut-derived active GLP-1 [23].…”
Section: Evidence For a Beneficial Effect Of Neprilysin Inhibition Onmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, recent literature suggests that elevated MME participates in the development of insulin resistance. On one hand, MME cleaves peptides stimulating insulin secretion, i.e., glucagon [40] and GLP1 (glucagon-like peptide 1) [41], and thus MME may reduce systemic insulin secretion [42]. On the other hand, membrane-associated MME modulates internalization and cellular localization of the insulin receptor, as shown by MME knockdown and overexpression in insulin target cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of glucagon and GLP-1 were recently reported in sepsis (11,12) and critically ill patients (13), in mice following LPS injection (23), and in humans with burn lesions(24). Estimation of plasma GLP-1 in mice is troublesome due to the rapid degradation by neprilysin (25,26), and the assays employed in the current human study and in other previously published studies also cross-react with GLP-1 1-36NH 2 that is cosecreted with glucagon (17). Therefore, one may speculate that the reported increases in GLP-1 actually reflect increased glucagon secretion from pancreatic alpha cells, as captured in the study presented here.…”
Section: Discussionmentioning
confidence: 93%